Advances in manufacturing and industrial engineering select proceedings of ICAPIE 2019 - Singari, Ranganath M.; Mathiyazhagan, Kaliyan; Kumar, Harish (Singapore Springer, 2021)
This book presents selected peer reviewed papers from the International Conference on Advanced Production and Industrial Engineering (ICAPIE 2019). It covers a wide range of topics and latest research in mechanical systems engineering, materials engineering, micro-machining, renewable energy, industrial and production engineering, and additive manufacturing. Given the range of topics discussed, this book will be useful for students and researchers primarily working in mechanical and industrial engineering, and energy technologies.
Electronic reproduction
Keywords: Manufacturing industries -- Technological innovations -- Congresses